The politics of prison nursing and HIV/AIDS at Pollsmoor maximum security prison 1990-2008 - Nzuza, Mpumelelo (Department of Historical Studies, 2026)
The purpose of this thesis is to examine histories of prison nursing and the management of HIV/AIDS at Pollsmoor Maximum Security Prison. South Africa is a country with a high HIV prevalence, with rates of infection being especially notable among prisoners. Extant studies of HIV/AIDS in prisons in South Africa have largely focused on inmates' experiences of receiving healthcare services in prisons. Focusing on the years 1990 to 2008, the thesis offers a social history of prison nursing over time with a focus on nurses' workplace experiences in dealing with HIV/AIDS in their patients. By investigating prison nurses' everyday realities, the thesis finds that they experience challenges because of experiencing a fraught dual-system dynamic as employees of the Department of Correctional Services (DCS) who also collaborate with those based at the Department of Health (DOH). The former also tends to prioritize security over inmates' access to quality healthcare. The thesis draws upon a range of sources, including 20 oral history interviews (16 with prison nurses, two with clinical practitioners, and two with non-clinical health practitioners from the NGO TB/HIV Care); prison laws and policies, and DCS annual reports. It reaches several conclusions, such as outlining how factors such as gangs, prison violence (including sexual assault), transactional sex, substance abuse, and overcrowding affect prisoners' vulnerability to infection and their uptake of HIV prevention services provided by the nurses. Concluding in 2008, this thesis captures the significant role played by NGOs and health activists who advocated for inmates' access to effective HIV prevention and treatment services. It describes how legal activism catalyzed the provision of antiretrovirals (ARVs); this, alongside the work of NGOs such as HIV/TB Care, dramatically improved nurses' ability to provide HIV prevention and treatment services.